2010
DOI: 10.1152/ajpheart.00018.2010
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside/nucleobase transport and metabolism by microvascular endothelial cells isolated from ENT1−/− mice

Abstract: Bone DB, Choi DS, Coe IR, Hammond JR. Nucleoside/nucleobase transport and metabolism by microvascular endothelial cells isolated from ENT1 Ϫ/Ϫ mice. Am J Physiol Heart Circ Physiol 299: H847-H856, 2010. First published June 11, 2010; doi:10.1152/ajpheart.00018.2010.-Nucleoside and nucleobase uptake is integral to mammalian cell function, and its disruption has significant effects on the cardiovasculature. The predominant transporters in this regard are the equilibrative nucleoside transporter subtypes 1 (ENT1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Genotyping was performed as described. (33) Given the increased reported prevalence of DISH in males (25% of men versus 15% of women over 50 years of age), (34) male mice were used for all experiments. Mice were euthanized at the following ages: 1 month (4-4.5 weeks), 2 months (8-11 weeks), 4 months (16-18 weeks), 6 months (26-30 weeks), and 12þ months (12-17 months).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotyping was performed as described. (33) Given the increased reported prevalence of DISH in males (25% of men versus 15% of women over 50 years of age), (34) male mice were used for all experiments. Mice were euthanized at the following ages: 1 month (4-4.5 weeks), 2 months (8-11 weeks), 4 months (16-18 weeks), 6 months (26-30 weeks), and 12þ months (12-17 months).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there is no significant difference in spontaneous mortality rates up to 6 months of age. To date, there have been no reports of phenotypic changes in skeletal tissues related to mineralization (32,33,41,42) ; however, all reported studies were conducted on mice less than 4 months of age.…”
Section: Ectopic Mineralization In Ent1 -/-Micementioning
confidence: 99%
“…Hypoxanthine uptake is neither inhibited by dipyridamole in mouse primary microvascular endothelial cells, which exhibit considerable transport activity of 2-chloroadenosine by Ent1, nor significantly altered in cells from Ent1-deficient mice. 34) However, one study reported the involvement of ENT1 in hypoxanthine transport in a murine T-lymphoma cell line, S49, which was mostly inhibited by 10 nM of NBMPR. 35) 4.2.…”
Section: Facilitative Transport Systemsmentioning
confidence: 99%
“…However, because the term "ENBT1" was previously used to denote a putative transporter and a system that mediates dipyridamole-insensitive hypoxanthine transport in cells such as primary human cardiac microvascular endothelial cells, 34,46,47) the use of "ENBT1" as an alias for SLC43A3 would cause confusion. The present review advocates the use of either SLC43A3 or the same alongside ENBT1.…”
Section: Enbt1/slc43a3mentioning
confidence: 99%
“…Nevertheless, the effect of prolonged activation of A1AR by CHA or adenosine on TGF responsiveness has not been examined. Finally, accelerated degradation of adenosine may affect TGF responses since an upregulation of adenosine deaminase has been found in microvascular endothelial cells of ENT1-deficient mice (2). This possibility cannot be excluded although we did not find an increased expression of adenosine deaminase mRNA in kidney tissue.…”
Section: F385 Type 1 Equilibrative Nucleoside Transporter and Tgfmentioning
confidence: 55%